Suplementasi Fitase, Seng dan Tembaga dalam Ransum Sebagai Stimulan Pertumbuhan Ayam Broiler - H Setiyatwan; W G Piliang; D.T H Sihombing; W Manalu; A Anang (Faculty of Animal Science, Bogor Agricultural University, 2007)
Zinc and Cu have important roles in growth and immune system, but their bioavailability are low due to the phytic acid content in poultry diet. This experiment was conducted in order to obtain the best combination of phytase, Zn, and Cu as growth stimulants for broiler fed diet containing phytic acid. Two hundred eighty eight Day Old Chicks unsexed were allocated into nine treatment diets with four replications (eight chicks in each replicate). The birds were raised up to 42 days old. Combination of the treatment diets were: R1 (positive control), R2 (negative control), R3 (R2 + 132.70 ppm ZnO), R4 (R2 + 286.16 ppm CuSO4), R5 (R2 + 132.70 ppm ZnO + 286.16 ppm CuSO4), R6 (R2 + phytase 1000 FTU/kg), R7 (R2 + phytase 1000 FTU/kg + 132.70 ppm ZnO), R8 (R2 + phytase 1000 FTU/kg + 286.16 ppm CuSO4 ), R9 (R2 + phytase 1000 FTU/kg + 132.70 ppm ZnO + 286.16 ppm CuSO4). The results of this research indicated that the phytase supplementation (1000 FTU/kg), ZnO (132.70 ppm), and CuSO4 (286.16 ppm) in poultry diet 1) improved the body weight and feed conversion, but did not significantly influence the feed consumption, 2) increased serum Zn, and 3) increased the alkalin and phosphatase activity. Key words: phytase, zinc, copper, broiler, growth stimulant